The use of minimum nitrogen requirements (N gaps) by Yara and IFA - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Yara and IFA adopted the minimum nitrogen requirements (N gaps), published in the Global Yield Gap Atlas (GYGA). They see the N-gaps as vital input to develop fertilizer recommendations, adapted to local conditions that will optimize yield and minimize greenhouse gas emissions.